PENERAPAN E-COMMERCE DALAM MENUNJANG PENJUALAN DOC (DAY OLD CHICK) ASP BREEDING FARM - Try Septiar Syamfithriani (Cloud Information, 2020)
Trading via the internet is a promising business opportunity and is becoming a trend nowadays. The ease in the process of buying and selling and transactions using technology support makes e-commerce trading growing rapidly. ASP Breeding Farm is a company engaged in the field of poultry shop, which produces products in the form of DOC (day old chick), but sales and marketing are still using traditional or conventional methods offline without using internet media, consequently the market is still limited. Therefore this research will develop the marketing and sales process from the conventional way to the digital way that is utilizing internet technology, namely building e-commerce aimed at developing market share and sales. The development of e-commerce uses tomatocart's content management system